2016
DOI: 10.11622/smedj.2016017
|View full text |Cite
|
Sign up to set email alerts
|

Non-fluoroscopic navigation systems for radiofrequency catheter ablation for supraventricular tachycardia reduce ionising radiation exposure

Abstract: INTRODUCTIONRadiofrequency catheter ablation (RFCA) is a first-line therapeutic option for supraventricular tachycardia (SVT).(1) It is conventionally performed under fluoroscopy. The amount of exposure to fluoroscopy is highly dependent on multiple variables, such as operator experience and the complexity of the arrhythmia substrate.(2) As exposure to radiation during such procedures increases the lifetime risk of fatal malignancies, skin injuries and cataract, it poses a palpable hazard to both patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Ensite NavX system can be used for accurate navigation. The advantages of three dimensional mapping system has been widely discussed in previous studies [8,12,[25][26][27][28][29]. According to our experience, the guidewires Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Ensite NavX system can be used for accurate navigation. The advantages of three dimensional mapping system has been widely discussed in previous studies [8,12,[25][26][27][28][29]. According to our experience, the guidewires Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Ventricular and atrial stimulation protocols were used to assess conduction properties and arrhythmia inducibility. Standard protocols and procedures, depending on the arrhythmic substrate, were used for all ablation procedures [12]. Fluoroscopy was used throughout all phases of the procedure, including confirmation of the guidewire position, electrophysiological studies, mapping, and ablation.…”
Section: Conventional Fluoroscopy (Cf) Approachmentioning
confidence: 99%
“…Furthermore, as the volume of atrial fibrillation procedures rises, concern over patient and staff radiation exposure continues to increase 2, 12, 13. While nonfluoroscopic guidance systems, such as ICE, TEE, and 3D EAM, have been increasingly used in catheter ablation procedures to reduce or completely eliminate fluoroscopy,4, 5, 6, 7, 8, 14 transseptal access is often regarded as the main challenge in completely nonfluoroscopic catheter ablation 15 . This step requires visualization of the drop-down of the device tip from the brachiocephalic vein or SVC to the fossa ovalis, which is traditionally performed under fluoroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, catheter ablations can be performed with minimal or even zero fluoroscopy, leading to significant reduction in radiation dose as well as fluoroscopy time . In addition, studies have shown that the minimal fluoroscopic technique was safe and did not compromise acute success rates …”
Section: Discussionmentioning
confidence: 99%